2020
DOI: 10.1002/edm2.111
|View full text |Cite
|
Sign up to set email alerts
|

Trauma exposure and stress‐related disorders in African‐American women with diabetes mellitus

Abstract: Objective:The purpose of the study was to assess demographic features, rates of trauma exposure, prevalence of post-traumatic stress and depressive symptoms in a group of urban, low-income, African-American women with type 1 or type 2 diabetes mellitus. Research Design and Methods:We conducted a survey of (n = 290) low-income, African-American women seeking care in the diabetes clinic of an urban hospital and collected data on the demographic characteristics, childhood and nonchildhood abuse trauma exposure, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Descriptive statistics on trauma exposure, PTSD symptoms, and racial discrimination for this sample of 55 Black women living in the US (mean [SD] age, 37.7 [10.7] years; range, 21-61 years) are provided in Table 1. Participants reported a mean (SD) TEI frequency of 33.0 (18.8) (similar to previous Grady Trauma Project studies [28][29][30] ) and showed moderate levels of current PTSD symptoms (mean [SD] PSS, 15.4 [12.9]). Racial discrimination (EOD) scores ranged from 0 to 9 and were moderately correlated with current PTSD symptoms (PSS total: r = 0.36; P = .009), but not with age (r = 0.20; P = .15) or TEI frequency (r = −0.02; P = .89).…”
Section: Ptsd Symptoms Trauma and Racial Discriminationsupporting
confidence: 75%
“…Descriptive statistics on trauma exposure, PTSD symptoms, and racial discrimination for this sample of 55 Black women living in the US (mean [SD] age, 37.7 [10.7] years; range, 21-61 years) are provided in Table 1. Participants reported a mean (SD) TEI frequency of 33.0 (18.8) (similar to previous Grady Trauma Project studies [28][29][30] ) and showed moderate levels of current PTSD symptoms (mean [SD] PSS, 15.4 [12.9]). Racial discrimination (EOD) scores ranged from 0 to 9 and were moderately correlated with current PTSD symptoms (PSS total: r = 0.36; P = .009), but not with age (r = 0.20; P = .15) or TEI frequency (r = −0.02; P = .89).…”
Section: Ptsd Symptoms Trauma and Racial Discriminationsupporting
confidence: 75%
“…Compared to non-Hispanic Whites, American Indians experience higher rates of post-traumatic stress disorder [29]. The co-occurrence of T2D and post-traumatic stress disorder is associated with worse diabetes-related health outcomes compared to T2D alone [25,26,28]. To date, only one study has examined post-traumatic stress and HRQoL among American Indians with T2D [28].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have examined the association of psychosocial factors, such as support, coping, resilience, and mental health [post-traumatic stress disorder (PTSD)] with HRQoL in non-Native populations [19][20][21][22][23][24][25]. For example, in a sample of older African Americans and Whites with diabetes, findings suggested that diabetes-specific social support was positively associated with HRQoL [20], and in a systematic review examining the relationship between resilience and chronic diseases findings indicated that lower levels of resilience were associated with poor HRQoL [23].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, biological, psychological, social, and environmental processes linking childhood experiences to adulthood routine diabetes care and self-management should be tested. For example, recent studies have identified adulthood mental health (Dixon et al, 2020), psychological distress (Strenth et al, 2022), and delay discounting (Shain et al, 2022) as potential mechanisms for explaining how childhood trauma relates to diabetes self-management in adulthood.…”
Section: Discussionmentioning
confidence: 99%